Forecasting of the productivity of parts machining by high-speed milling with the method of half-overlap - Dobrotvorskiy, S. S.; Basova, Ye. V.; Ivanova, M. S.; Kotliar, A. V.; Dobrovolska, L. G. (Polish Society of Technical Diagnostics, 2018)
In the article the technology of high-speed milling was observed as a key to the most promising methods of engineering products machining. It is indicated that the correct choice of the strategy for moving the cutting tool in the manufacture of products is the basis for ensuring the desired surface quality of the workpiece and its high processing efficiency. A review of the work devoted to the diagnosis of high-speed processing strategies was performed. Based on the up-to-date knowledge of the physics of the process of establishing of a qualitative surface, the article proposes to consider a new technology of high-speed milling with half-overlap. As the main idea of this technology, it is suggested to consider the work of the deformation component of cutting process as the main component of the complex energy-intensive process of high-speed milling. In addition, the paper suggests a technique for estimating the productivity of machining by the method of high-speed milling with half-overlap. It is theoretically justified that the specific productivity of the proposed technology is quite high Q=12.5÷4.2 cm2/min and depends on the technological regimes. The place of technology of high-speed milling with half-overlap in the technological process of manufacturing details of any complexity was noted. The area of further research is indicated.
Keywords: high-speed milling; processing efficiency; processing strategy; half-overlap; deformation component